Pengaruh konsentrasi ekstrak daun bambu (Gigantochloa apus) dan konsentrasi starter terhadap kadar total flavonoid, pH dan organoleptik pada yoghurt - Vita Lestari Catur Intani; Muh. Aniar Hari Swasono (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Bamboo leaf extract contains flavonoids which have many benefits and herbal properties. The purpose of this study was to determine the effect of concentration of bamboo leaf extract and concentration of starter on total flavonoid content, pH value and yogurt organoleptic. This research was conducted using a Randomized Block Design (RAK) with 2 factors. Factor I was the concentration of bamboo leaf extract (5%, 10%, 15%) and factor II was the concentration of starter (4%, 5%, 6%). Parameters tested were total flavonoid content, pH and organoleptic (hedonic test). The results showed that the concentration of addition of fresh bamboo leaf extract and starter concentration had a very significant effect on total flavonoid levels. The pH value tends to decrease with increasing concentration of bamboo extract which is added to the manufacture of bamboo leaf yogurt. The concentration of starter used in making yogurt has a significant effect on the pH value of bamboo leaf yogurt. The best treatment results were yogurt with a concentration of 15% bamboo leaf extract and a starter concentration of 4% with a total flavonoid content of 560.89 mg EQ/ml, a pH value of 5.6, a preference scale for taste 3.82, color 3.02 and texture 3.3.